The relation between the excited electronic states of acene radical cations and neutrals: a computational analysis - Weidlich, Anna; Dreuw, Andreas (Journal of computational chemistry, 2025)
Acenes are a class of molecules that enjoy popularity in both experimental and theoretical fields of research for their diverse areas of application and unique electronic structure. One particular aspect of interest lies in their electronic absorption spectra, which have been thoroughly investigated both experimentally and theoretically. In this work, the electronically excited states of radical cations of acenes from naphthalene to dodecacene are investigated using algebraic diagrammatic construction (ADC) methods and different time-dependent density functional theory (TD-DFT) exchange-correlation kernels. The performance of the employed ADC methods and different DFT functionals is assessed using experimental values as benchmarks. Using ADC, it is then shown that excited states typical for neutral acenes are retained in their radical cation counterparts, while additional states emerge due to excitations into the singly-occupied molecular orbital (SOMO). Finally, the evolution of the excitation energies in neutral as well as cationic acenes with increasing length is investigated using TD-DFT, where a special focus lies on the correct description of longer acenes using single-reference methods.
Erstveröffentlichung am 08. April 2025
Gesehen am 01.10.2025